Synthesis of N-Doped Porous Carbon Materials Derived from Waste Cellulose Acetate Fiber via Urea Activation and Its Potential Application in Supercapacitors. Issue 6 (1st January 2019) - Cheng, Youliang; Zhang, Qingling; Fang, Changqing; Huang, Zhigang; Chen, Jing; Wu, Linlin; Wang, Hongtao
Abstract : The N-doped porous carbon materials were prepared via the co-carbonization of cellulose acetate fiber and urea. The cellulose acetate fiber was derived from waste cigarette and urea was used as the nitrogen source and the activating agent. The carbonization temperature has an important effect on the specific surface area, porosity and nitrogen content of as-prepared porous carbon materials. When the carbonization temperature was 750°C, as-prepared CN-750 with an average pore size of 4.84 nm exhibited the highest specific surface area of 734 m 2 ·g −1 . The sample of CN-600 synthesized at 600°C showed the highest nitrogen content of 11.69 at%. Moreover, as-prepared samples with disordered pores showed a low graphitization degree and a large interlayer space. The specific capacitance of CN-750 is 152 F·g −1 at the current density of 1 A·g −1, which is higher than that of CN-600 and CN-900. After 5000 cycles, the capacitance retention of CN-600, CN-750 and CN-900 is 91.9%, 93.1% and 95.1%, respectively. The energy density of CN-750 is 5.28 Wh·kg −1 at the power density of 250.1 W·kg −1 and it retains 6.09 Wh·kg −1 at the power density of 24.97 W·kg −1 . Our study indicates that the waste cigarette butts can be effectively recycled via the co-carbonization method, and as-prepared N-doped porous carbon materials with an excellent cycling stability and a reasonable availability are promising candidates for the electrode materials of supercapacitors.